Gold extraction at the molecular level using α- and β-cyclodextrins - Braga, Susana Santos (Beilstein Journal of Organic Chemistry, 2025)
Cyclodextrins (CDs) are known for their ability to form supramolecular interactions with a wide range of guest molecules. In this review, focus is given on the inclusion of complex aurate ions such as tetrabromoaurate, dicyanoaurate and a few other tetrahaloaurates. The review describes the properties of self-assembly of cyclodextrins with these ions, with highlight to α-CD and, more recently, β-CD, requiring the use of a co-former/precipitating agent. Practical applications of this ability are directed to the selective isolation of gold from a variety of sources, spanning from gold-rich mining ores and tailings/mining wastes to gold-bearing metal scraps obtained from disposed electronic devices. Moreover, it describes the development of a method based on spontaneous complex formation between α-CD and tetrabromoaurate and its current status of use in a few mining sites in the United States.
Keywords: bromoaurate; cyanoaurate; cyclodextrin inclusion; self-assembly; supramolecular interactions